Kualitas Pelayanan Penyaluran Bantuan Raskin di Kelurahan Panarung Kota Palangka Raya - Muhamad Yusuf; Novia Lestari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
This study aims to describe and describe the Quality of Service for the Distribution of Raskin Assistance in Panarung Village, Palangkaraya City. The research method used is qualitative where the researcher wants to describe and describe the Quality of Service for Distribution of Raskin Assistance in Panarung Village, Palangkaraya City, Data Sources namely Social Welfare and Community Services Section, Development and Human Resources (HR) section and Government section. Based on the results of research that has been conducted that the Quality of Service Delivery of Raskin in Panarung Urban Village, Palangkaraya City is quite good and its implementation has followed established procedures, but it is still not optimal, because socialization is not maximized, inadequate facilities, disciplinary officers that makes service slow